Implementasi E-Government dalam Meningkatkan Transparansi dan Akuntabilitas Pelayanan Publik di Era Digital - Fadli Mappisabbi; Abd Haris; Wahyudin Zuhri (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
This study analyzes the implementation of e-government as an instrument in increasing transparency and accountability of public services in the digital era. Using a qualitative approach and case studies in several government agencies, this study shows that the implementation of e-government has a significant impact on increasing transparency through easy access to public information and accountability through a more effective tracking and monitoring system. However, there are various challenges in its implementation, including the digital divide, limited technological infrastructure, and resistance to organizational change. This study recommends a comprehensive strategy that includes developing human resource capacity, improving technological infrastructure, and strengthening the regulatory framework to optimize the benefits of e-government in more transparent and accountable governance.